Penerapan teknik buteyko breathing exercise terhadap pernapasan SPO2 pada klien bronkopneumonia dengan masalah keperawatan pola nafas tidak efektif - Dalimunthe, Najamudin; Trismiyana, Eka; Djamaludin, Djunizar (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Pneumonia remains the fifth leading cause of death worldwide. Indonesia accounts for 28 deaths per 100,000 people annually. Most confirmed cases are in adults aged 45-65 years (18%) and children aged 0-4 years (14.4%). Data from South Lampung in 2022 showed 972 cases of pneumonia. Purpose: To provide geriatric nursing care to clients with bronchopneumonia who experience ineffective breathing patterns, using the Buteyko breathing exercise technique. Method: This descriptive case study design involved two subjects, each with an ineffective breathing pattern. The study was conducted at the Branti Raya Natar Community Health Center in South Lampung. Patients received non-pharmacological nursing care with Buteyko breathing exercises, performed three times daily (morning, afternoon, and evening) for four weeks. Results: Nursing management of ineffective breathing patterns with the application of Buteyko breathing exercise techniques that the author carried out for 3 days on bronchopneumonia patients with ineffective breathing patterns in both clients was resolved, as evidenced by the normal breathing frequency of clients Mr. K and Mr. S and during the second procedure the clients were cooperative. Conclusion: There is an effect of the application of the Buteyko breathing exercise technique in reducing the breathing frequency in bronchopneumonia patients. Keywords: Bronchopneumonia; Buteyko Breathing Exercise; Ineffective Breathing Pattern. Pendahuluan: Pneumonia saat ini masih menjadi salah satu penyebab kematian yang menempati nomor lima di dunia. Terdapat 28 kematian per 100.000 penduduk di Indonesia setiap tahunnya. Sebagian besar di antara kasus terkonfirmasi adalah orang dewasa usia 45-65 tahun (18%) dan anak-anak usia 0-4 tahun (14.4%). Data di Lampung Selatan tahun 2022 mendapatkan data pneumonia sebanyak 972 kasus. Tujuan: Untuk melakukan asuhan keperawatan gerontik pada klien bronkopneumonia dengan masalah keperawatan pola nafas tidak efektif dengan penerapan teknik buteyko breathing exercise. Metode: Penelitian deskriptif dengan rancangan studi kasus menggunakan 2 subjek yaitu orang yang mengalami masalah keperawatan pola nafas tidak efektif. Tempat penelitian dilaksanakan di Wilayah Puskesmas Branti Raya Natar Lampung Selatan. Pasien diberikan asuhan keperawatan terapi non farmakologi dengan latihan pernapasan buteyko dilaksanakan 3 kali sehari (pagi, siang, dan malam) selama 4 minggu. Hasil: Pengelolaan keperawatan pola nafas tidak efektif dengan penerapan tindakan keperawatan teknik buteyko breathing exercise yang penulis lakukan selama 3 hari pada pasien bronkopneumonia dengan masalah pola nafas tidak efektif kedua klien teratasi semua dibuktikan dengan klien Tn. K dan Tn. S frekuensi nafasnya normal dan selama tindakan kedua klien kooperatif. Simpulan: Terdapat pengaruh penerapan teknik buteyko breathing exercise untuk mengurangi frekuensi nafas pada pasien bronkopneumonia. Kata Kunci : Bronkopneumonia; Buteyko Breathing Exercise; Pola Nafas Tidak Efektif.